The Reported Pain Coping Strategies of Pediatric Burn Survivors—Does a Correlation Exist Between Coping Style and Development of Anxiety Disorder?. Issue 2 (March 2015) - Rimmer, Ruth Brubaker; Alam, Now Bahar; Bay, R. Curt; Sadler, Ian J.; Foster, Kevin N.; Caruso, Daniel M.
<x xml:space="preserve">Abstract</x> Unresolved pediatric pain, both acute and chronic, has been associated with negative short- and long-term physical and mental health outcomes. This study sought to determine whether an association existed between self-reported pain coping skills and anxiety levels in a cohort of pediatric burn patients, and whether gender would influence their responses. The sample comprised burn-injured children in attendance at one of three mature burn camp sites. The self-report measures utilized included the 41-item Screen for Child Anxiety Related Disorders Child Version and the 39-item Pain Coping Questionnaire. Parental consent was obtained. A psychologist administered the measures. Participants included 187 youth, mean age 12.4 ± 2.4 years, girls (n = 89) boys (n = 98) with 67% reporting visible burn scars. Among boys, the use of Internalizing Coping Strategies was moderately correlated with elevated scores on Panic Disorder symptoms (r = .42, P < .001). Among girls, the use of Internalizing Coping Strategies was associated with elevated Generalized Anxiety (r = .51, P < .001), Panic Disorder (r = .46, P < .001), and Total Anxiety Symptom Scores (r = .49, P < .001). Those children who reported using Behavioral Distraction Strategies did not have any elevated anxiety scores. These findings suggest that burn-injured children, who employ Internalization as their pain coping strategy, may be more vulnerable to the development of long-term anxiety disorder, which, if left untreated may result in a negative psycho/social outcome. Applicability to Practice: Assessment of in-patient pediatric patients with the Pain Coping Questionnaire may help to identify children who are more likely to experience long-term anxiety. Future studies should seek to confirm these findings and determine whether improved pain management and early treatment of anxiety can help to diminish the long-term implications of unhelpful pain strategies and increased anxiety in burn-injured children.